اتحادِ امت کا خواب: اسلامی تعلیمات ، سلف کا طرز عمل اور معاصر مسلمانوں سے مطلوب رویہ: The Dream of Unity of Ummah: Islamic teachings, Conduct of the Salaf and the attitude required of Contemporary Muslims - Majid Rashid; Muhammad Anwar Farooq (Al-Qamar, 2019)
Candidly, without unity and accord it is not possible to develop a nation. In this rapidly changing world the problems for Muslims are increasing day by day and reason behind such deteriorated situation is sectarianism, prejudices, intolerance and many other materialistic interests. All these evils have been denounced in true Islamic teachings. Allah has directed Muslims to observe tolerance and hold solidarity among them. It also remains the main obligation of the Muslim rulers to assume their job in this regard. This paper is an effort to describe Islamic teachings about unity of Muslims and the behavior Islam demands from the contemporary Muslims.